Bremer Key: The Development and Validation of a Child-Sensitive Language Competence Test for Teachers - Rotschild, Tamas (Przegląd Psychologiczny, 2024)
Aim: Language is a powerful instrument of educators, yet it is anything but neutral, carrying nuanced meanings that extend beyond the literal. These nuances, laden with emotions and evaluations, exert a cumulative impact on the inner worlds of children. Therefore, a high level of child-sensitive language (CSL) competence is essential for teachers. Method: To enhance prospective teachers’ language competence, a Situational Judgment Test (SJT) was developed and validated as part of doctoral research at the University of Bremen, Germany. The test items and response options were developed by a team of three in-service teachers, led by the doctoral researcher, and supported by two university professors with expertise in the field, following established development practices. Results: Pilot testing involved 47 in-service teachers from multiple public schools and 55 university students across three institutions. Following iterative refinement, the test was finalized with 13 items, demonstrating strong internal consistency indicated by a computed value of ⍵ = 0.81. The test and its utility were positively evaluated by the participants. Conclusion: The study concludes that this instrument can be utilized across various educational domains and teacher training programs to enhance educational practices and outcomes.